Pengaruh Ekstrak Etanol Herba Ginseng Sumatera (Talinum triangulare (Jacq. ) Willd) Terhadap Aktivitas SGOT Dan SGPT Pada Serum Darah Mencit Putih Jantan Yang Terinduksi Karbontetraklorida - Elisma Elisma; Ella Handalia; Helmi Arifin (Jurnal Farmasi Higea, 2011)
Influence of the ethanolic extracts of Sumateran ginseng (Talinum triangulare  (Jacq.) Willd) on SGOT and SGPT activities in serum of male mice induced CCl4 has been done. The extract was given orally once a day for 14, 21, and 28 days respectively,at various doses 125, 250, and 500 mg/kg BW. The group of mice treated with Na CMC 0,5 % was used as control. The results suggest a possible hepatoprotective potential of the ethanol extract of Talinum triangulare  can decrease the SGOT and SGPT activities on male mice induced CCl4.